2019
DOI: 10.21475/ajcs.19.13.02.p1312
|View full text |Cite
|
Sign up to set email alerts
|

Performance of upland rice cultivars at different sowing times: an alternative for crop rotation in low altitude Cerrado region, Brazil

Abstract: The adequacy of the best sowing times and the choice of rice cultivars is determinant for greater investment and return in upland rice cultivation. Thus, this study identified the best sowing time and the cultivar that expresses its yield potential, being adaptable and stable, in a low altitude Cerrado region. The study was conducted during the agricultural year 2016/17. The soil of the site is a typical clayey dystrophic Red Latosol. The experimental design was in randomized blocks, in factorial scheme with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the third year, there was more accumulated precipitation and better distribution ( Figure 1C), indicating that there were more cloudy days and, consequently, lower solar radiation incidence in relation to the second year ( Figure 1B). Meirelles et al (2019) reported that lower incidence of solar radiation reduces the photosynthetic process and leads to a decrease in the number of panicles m -2 in rice plants. Owing to the greater formation of panicles in the present study, there was less formation of spikelets per panicle, indicating possible competition within the plant for photoassimilates.…”
Section: Continuationmentioning
confidence: 99%
“…In the third year, there was more accumulated precipitation and better distribution ( Figure 1C), indicating that there were more cloudy days and, consequently, lower solar radiation incidence in relation to the second year ( Figure 1B). Meirelles et al (2019) reported that lower incidence of solar radiation reduces the photosynthetic process and leads to a decrease in the number of panicles m -2 in rice plants. Owing to the greater formation of panicles in the present study, there was less formation of spikelets per panicle, indicating possible competition within the plant for photoassimilates.…”
Section: Continuationmentioning
confidence: 99%
“…The farmers adopting Bhur Kambja-1 in southern Bhutan under wet-subtropical zone may consider this as optimum sowing window. However, this result may not to imply to other varieties as findings of significant interaction between sowing time and rice varieties was reported by (Fagahni et al,2011), (Safdar et al, (2013), (Khalifa et al 2014), and (Meirelles et al 2019). However, farmers with no assured irrigation may adopt Bhur Kambja-1 in times of delayed monsoon with expected yield reduction reported in this study.…”
Section: Recommendation and Conclusionmentioning
confidence: 54%
“…With no N fertilizer application, rice yield was greater when monocropped than in the intercropping systems, and this difference increased as the rate of N fertilizer application increased. In the intercropping systems, forage grasses shaded rice plants due to vigorous growth of the grasses, and the consequent lower solar radiation on the rice leaves reduced plant development and photosynthetic processes during grain filling (Meirelles et al, 2019).…”
Section: Upland Ricementioning
confidence: 99%